Genetic Recombination for Antigenic Markers of Antigenically Different Strains of Influenza B Virus - Tobita, K. (1974)
Incorporation of trypsin in agar overlay or fluid maintenance media resulted in enhancement of plaquing efficiency and replication of influenza B viruses in primary chicken embryo fibroblasts. Using this improved technique, recombination was attempted with two serologically distinct strains of influenza B virus, B/Lee/40 and B/Massachusetts/1/71. After mixed infection, two virus clones were selected and characterized in detail. Hemagglutination inhibition and neuraminidase inhibition tests showed that these viruses are reciprocal antigenic recombinants with hemagglutinin derived from one parent and neuraminidase from the other. Serological examinations of the antisera to these recombinants confirmed the results. The frequency of recombination was high in the present system and 64% of the virus clones isolated without selection from the mixed yield were recombinants. This high recombination frequency is consistent with the genomic reassortment that is characteristic of recombination of influenza A viruses.